Doubtful debt: the rising cost of student loans - Cherastidtham, Ittima; Norton, Andrew (Grattan Institute, 2014)
By 2017 the Government will have $13 billion of student loans on its books that it does not expect to collect. With modest reforms it could recoup $800 million a year while still meeting the loan scheme’s goals.
Doubtful debt: the rising cost of student loans
Keywords: Income & Finance -- Debt; Education and Training -- Tertiary; Education and Training -- Costs; Income, wealth and finances; Learning, education and training; Education and Training; Income & Finance; Tertiary; Debt; Costs; Income, wealth and finances; Learning, education and training